PENDIDIKAN SEKOLAH RAKYAT DAN SEKOLAH GARUDA SEBAGAI BENTUK IMPLEMENTASI EKSKLUSI SOSIAL - Nuris watunnaba; Megawati Rusdianto (FISIP Universitas Malikussaleh, 2026)
This article aims to analyze the education policies behind the development of Sekolah Rakyat for deprived groups and Sekolah Garuda, which was established as a model of elite schools in several regions. It examines the impact of these two policies through the theoretical perspectives of Tan Malaka and Michel Apple, both of whom criticize education as often being non-neutral, excluding the poor through systems that differentiate individuals based on social class and creating “favorite schools.” Such practices indirectly lead to unequal educational distribution between schools. This study uses a qualitative research method with a literature review approach, drawing from previous studies and official data from the Ministry of Education, Ministry of Social Affairs, and Statistics Indonesia. The findings show that education indirectly produces social exclusion for deprived communities, evident in the differing goals, visions, curricula, and admission processes between Sekolah Rakyat and Sekolah Garuda. The development of these school’s neglects improvements in access to education for economically and demographically excluded populations. The study offers solutions for creating an inclusive and equitable education system, ensuring all communities receive fair and adequate educational opportunities.